2008
DOI: 10.1186/1471-2334-8-36
|View full text |Cite
|
Sign up to set email alerts
|

A survey of knowledge, attitudes and practices towards avian influenza in an adult population of Italy

Abstract: Background: Several public health strategic interventions are required for effective prevention and control of avian influenza (AI) and it is necessary to create a communication plan to keep families adequately informed on how to avoid or reduce exposure. This investigation determined the knowledge, attitudes, and behaviors relating to AI among an adult population in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
94
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 11 publications
13
94
7
Order By: Relevance
“…This finding is not corresponding to a KAP study performed in Egypt where 67.6% of respondents mentioned avoiding contact with sick birds (Ismail and Ahmed, 2010). In the present study 60% respondents believed that AI is a serious disease, this finding is not compatible with earlier KAP study performed in Egypt in which 99% believed that it is a serious disease (Ismail and Ahmed, 2010)but similar to the results of KAP study conducted in Italy (Abbate et al, 2006;Giuseppe et al, 2008). Regarding to seriousness, around 66% respondents agreed that AI could be prevented which agree with the positive attitude of 79%, 53% and 71% respondents reported earlier (Fatiregun and Saani, 2008;Giuseppe et al, 2008;Najimi and Golshiri, 2013).…”
Section: Results and Discussion Socio-demographic Characteristics Of supporting
confidence: 69%
See 2 more Smart Citations
“…This finding is not corresponding to a KAP study performed in Egypt where 67.6% of respondents mentioned avoiding contact with sick birds (Ismail and Ahmed, 2010). In the present study 60% respondents believed that AI is a serious disease, this finding is not compatible with earlier KAP study performed in Egypt in which 99% believed that it is a serious disease (Ismail and Ahmed, 2010)but similar to the results of KAP study conducted in Italy (Abbate et al, 2006;Giuseppe et al, 2008). Regarding to seriousness, around 66% respondents agreed that AI could be prevented which agree with the positive attitude of 79%, 53% and 71% respondents reported earlier (Fatiregun and Saani, 2008;Giuseppe et al, 2008;Najimi and Golshiri, 2013).…”
Section: Results and Discussion Socio-demographic Characteristics Of supporting
confidence: 69%
“…The study had similar findings with compared to study conducted in China, Thailand, Indonesia, Myanmar and Nepal. Illiteracy is the main factor which hinders the awareness regarding to AI (Giuseppe et al, 2008). The findings about the respondents heard about AI differ from a previous survey conducted in Bangladesh, where 40% and 10% respondents from Rajshahi and Netrokona had heard about AI respectively (Sultana et al, 2011).…”
Section: Results and Discussion Socio-demographic Characteristics Of contrasting
confidence: 56%
See 1 more Smart Citation
“…These results support previous fi ndings that knowledge about avian infl uenza, especially about prevention and human-to-human transmission, has scope for improvement (4,5). Persons in Europe reported that they have little ability to prevent themselves from getting avian infl uenza (6).…”
Section: Knowledge About Avian Infl Uenza European Regionsupporting
confidence: 81%
“…Knowledge, Attitude and Perception (KAP) analysis is performed by some workers to evaluate the impact of one health intervention programmes. The knowledge refers to the degree of understanding on associated issues; attitude implies to the feelings of respondents to the understanding and perception is nothing but the awareness on the topic (Di Giuseppe et al, 2008). Narrod et al, (2011) applied the KAP analysis on pathogenic avian influenza outbreaks in African countries.…”
Section: Indian Perspectivementioning
confidence: 99%